2007
DOI: 10.1021/jp075663i
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Proton Transfer in Aqueous Acid−Base Reactions

Abstract: We study the mechanism of proton transfer (PT) in the aqueous acid-base reaction between the photoacid 8-hydroxy-1,3,6-pyrenetrisulfonic acid (HPTS) and acetate by probing the vibrational resonances of HPTS, acetate, and the hydrated proton with femtosecond mid-infrared laser pulses. We find that PT takes place in a distribution of hydrogen-bound reaction complexes that differ in the number of water molecules separating the acid and the base. The number of intervening water molecules ranges from 0 to 5, which,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
224
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(229 citation statements)
references
References 43 publications
5
224
0
Order By: Relevance
“…13 Recently, the proton transfer between HPTS and different carboxylate bases dissolved in water has been studied by probing the vibrations of the photoacid and an accepting base with femtosecond midinfrared laser pulses. [14][15][16][17][18][19][20][21] These studies showed that the SCK model does not provide an adequate description of the data at all delay times. It was also found that there is not a single well-defined reaction distance at which proton transfer takes place.…”
Section: -3mentioning
confidence: 98%
See 2 more Smart Citations
“…13 Recently, the proton transfer between HPTS and different carboxylate bases dissolved in water has been studied by probing the vibrations of the photoacid and an accepting base with femtosecond midinfrared laser pulses. [14][15][16][17][18][19][20][21] These studies showed that the SCK model does not provide an adequate description of the data at all delay times. It was also found that there is not a single well-defined reaction distance at which proton transfer takes place.…”
Section: -3mentioning
confidence: 98%
“…12,[14][15][16][17][18][19][20][21] If the strength and concentration of the base are sufficient, the release of the proton by HPTS * is strongly accelerated. In this acid-base reaction, the diffusion of the reactants through the water medium can play an essential role, as the reactants have to come sufficiently close to let the proton transfer take place.…”
Section: -3mentioning
confidence: 99%
See 1 more Smart Citation
“…Proton transfer is one of the most important reactions in acidbase chemical and biological dynamics caused by the site-specific interaction such as hydrogen bonding [24][25][26][27][28][29]. The skeletal mechanistic picture proposed by Grotthuss is still a guide for our understanding of the proton hopping in hydrogen-bonded systems [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The well-known Eigen-Weller model has frequently been utilized to depict the ESPT as a two-step process [20,21]: the acidic proton is transferred from the acid to a base molecule after photoexcitation, to form a contact ion pair and subsequently the contact ion pair is separated by diffusion. Recently, the bridging role of water in the proton exchange between an acid and a base in aqueous solution has been demonstrated [22]. However, many details of the proton transfer from photoacid to water remain elusive, for example, the structure and stability of the contact ion pair between the photoacid and the hydrated proton in the Eigen-Weller model.…”
Section: Introductionmentioning
confidence: 99%